PRESERVATION AND UTILIZATION OF LAKE ANEUK LAOT AS A SOURCE OF SOCIAL LIVELIHOOD FOR THE COMMUNITY IN SABANG CITY - Abdullah, Munawiah; Naxrasya, Dhyaake; Ahmad, Muhammad Yunus; Mukhtar, Marduati; Rambely, Nurul Aliyah Sham Binti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Aneuk Laot Village is home to a lake that serves as the primary source of livelihood for the local community. Residents play a vital role in maintaining the lake’s sustainability through mutual cooperation and adherence to rules that prohibit littering in the surrounding area. This reflects a strong collective spirit toward environmental preservation. This study aims to describe the level of community participation in preserving Lake Aneuk Laot, to understand the lake’s functions and benefits for residents, and to analyze the government's role in conservation efforts. A qualitative approach with descriptive research methods was used. Data were collected through observation, interviews, and documentation. Analysis was carried out through data reduction, presentation, and verification. The findings show that the residents of Aneuk Laot Village actively contribute to the preservation of the lake, demonstrating high awareness by avoiding actions that cause pollution, such as littering. This individual and collective awareness significantly supports the lake’s sustainability. Lake Aneuk Laot provides essential benefits, such as a source of clean water for daily needs and irrigation for nearby crops. For local fishermen, it offers a steady source of income. The government supports sustainability through communication, monitoring, and protective actions to safeguard the lake from various threats.